Growth behavior of fatigue cracks in ultrafine grained Cu smooth specimens with a small hole - Masahiro Goto; Kakeru Morita; Junichi Kitamura; Takaei Yamamoto; Masataka Baba; Seung-zeon Han; Sangshik Kim (Fracture and Structural Integrity)
In order to study the growth mechanism of fatigue cracks in ultrafine grained copper, stress controlled fatigue tests of round-bar specimens with a small blind hole as a crack starter were conducted. The hole was drilled on the surface where an intersection between the shear plane of the final ECAP processing and the specimen surface makes an angle of 45° or 90° with respect to the loading axis. At a low stress ( a = 90 MPa), the direction of crack paths was nearly perpendicular to the loading direction regardless of the location of the hole. Profile of crack face was examined, showing the aspect ratio (b/a) of b/a = 0.82. At a high stress ( ? a = 240 MPa), although the growth directions inclined 45° and 90° to the loading-axis were observed depending on the location of the drilling hole, crack faces in these cracks were extended along one set of maximum shear stress planes,  corresponding to the final ECAP shear plane. The value of aspect ratios was b/a = 0.38 and 1.10 for the cracks with 45° and 90° inclined path directions, respectively. The role of deformation mode at the crack tip areas on crack growth behavior were discussed in terms of the mixed-mode stress intensity factor. The crack path formation at high stress amplitudes was affected by the in-plane shear-mode deformation at the crack tip.